Conference Review EXAR Tagung 2012, Brugg (CH) - Roeland P Paardekooper (EXARC Journal)
In early October 2012, EXAR held its yearly conference in Brugg, Switzerland. EXAR is the European Association for experimental archaeology and has over 150 members. Their highlight is their annual conference and the proceedings, which usually appear 12 months later, which is very fast. In Switzerland, the proceedings of Schleswig 2011 were presented, and were almost 300 pages thick.